Inovasi Sosial Tubanan Agrocyrcleforestry: Sebuah Studi Menggunakan Metode Social Return On Investment (SROI) - A. Khoirul Anam; Arifin, Miftah; Mahaputra, Wahyu; Ilham, Ahmad (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: The study aims to assess the value of the impact of PT PLN UIK TJB's CSR program on the implementation of social innovation in Tubanan agroforestry. In this approach, the effect of the program has an essential meaning for the beneficiaries of the program, namely the farming community group in Tubanan Village. Design/Methode/Approach: This study used social return on investment (SROI) as a research methodology. This research was conducted on the beneficiaries of the Tubanan agroforestry program and considered all stakeholders directly or indirectly involved in the program. The research informants numbered 20 people who were members of the LMDH Tunas Agung in Tubanan Village. Research Finding: The results showed that the CSR programs generated social benefits on investment and provided economic, social, and environmental benefits. SROI as a solution that changes the mindset of investment analysis based on outcomes is not just output. Theoretical contribution/Originality: This study allows us to expand the evidence of the critical role of social innovation for farming community groups, but so far, little has been studied about the application of SROI as an assessment methodology. Practitionel/Policy implication: The results of the SROI analysis become the basis for improving the planning of subsequent CSR programs. Research limitation: The selection of financial results and the proxies used are potentially biased, even though the proxies have been quantified over a potential range, the impact value has been reduced by filters (deadweigh, attribution, displacement, drop-off), and only emphasizes the impact on hard results rather than soft ones, which are considered less valuable.